Corporations, Stakeholders and Sustainable Development I: A Theoretical Exploration of Business–Society Relations - Steurer, Reinhard (Journal of business ethics, 2005)
Sustainable development (SD) – that is, “Development that meets the needs of current generations without compromising the ability of future generations to meet their needs and aspirations” – can be pursued in many different ways. Stakeholder relations management (SRM) is one such way, through which corporations are confronted with economic, social, and environmental stakeholder claims. This paper lays the groundwork for an empirical analysis of the question of how far SD can be achieved through SRM. It describes the so-called SD–SRM perspective as a distinctive research approach and shows how it relates to the wider body of stakeholder theory. Next, the concept of SD is operationalized for the microeconomic level with reference to important documents. Based on the ensuing SD framework, it is shown how SD and SRM relate to each other, and how the two concepts relate to other popular concepts such as Corporate Sustainability and Corporate Social Responsibility. The paper concludes that the significance of societal guiding models such as SD and of management approaches like CSR is strongly dependent on their footing in society.